2022
DOI: 10.1002/acr.24728
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Patterns of Hydroxychloroquine and Glucocorticoids Among Lupus Patients After New‐Onset End‐Stage Renal Disease

Abstract: Objective. Optimal strategies for managing lupus medications after end-stage renal disease (ESRD) have not been addressed. The objective was to identify the current US-wide prescribing patterns of hydroxychloroquine (HCQ) and oral glucocorticoids (GS) among systemic lupus erythematosus (SLE) patients with incident ESRD enrolled in the US Renal Data System (USRDS) registry.Methods. We identified incident ESRD patients age ≥18 years with SLE as a primary cause of ESRD between January 2006 and June 2013. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Hydroxychloroquine (HCQ), belongs to the 4­aminoquinolines class with antimalarial activity and an immunomodulatory effect (Schrezenmeier and Dörner 2020 ; Munguía-Realpozo et al, 2021 ; Gupta et al 2022 ). It has also been used clinically in the treatment of systemic lupus erythematosus (SLE) (Costedoat-Chalumeau et al 2014 ; Broder et al 2021 ), downregulating pro-inflammatory cytokines and immunoglobulin, eliminating autoreactive lymphocytes, ultimately improves patient survival and relieves severe lupus symptoms (Takamasu et al 2019 ; Ponticelli and Moroni 2017 ; Willis et al 2012 ; Rainsford et al 2015 ). Some studies have shown that HCQ mainly accumulates in acidic vesicular lysosomes, affects the functions of proteasomes by increasing intracellular vacuolar pH, and also inhibits the functions of endolysosomes regulating autophagy, calcium signaling, and toll-like receptor (TLR)-mediated immune responses (Wu et al 2017 ; Wallace et al 2012 ; Nirk et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxychloroquine (HCQ), belongs to the 4­aminoquinolines class with antimalarial activity and an immunomodulatory effect (Schrezenmeier and Dörner 2020 ; Munguía-Realpozo et al, 2021 ; Gupta et al 2022 ). It has also been used clinically in the treatment of systemic lupus erythematosus (SLE) (Costedoat-Chalumeau et al 2014 ; Broder et al 2021 ), downregulating pro-inflammatory cytokines and immunoglobulin, eliminating autoreactive lymphocytes, ultimately improves patient survival and relieves severe lupus symptoms (Takamasu et al 2019 ; Ponticelli and Moroni 2017 ; Willis et al 2012 ; Rainsford et al 2015 ). Some studies have shown that HCQ mainly accumulates in acidic vesicular lysosomes, affects the functions of proteasomes by increasing intracellular vacuolar pH, and also inhibits the functions of endolysosomes regulating autophagy, calcium signaling, and toll-like receptor (TLR)-mediated immune responses (Wu et al 2017 ; Wallace et al 2012 ; Nirk et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%